Analisis Strategi Pendidikan Islam dalam Membentengi Karakter Siswa dari Pengaruh Negatif Era Digital - Nanda Safira Sinaga; Era Duha Kaida Tama; Mazidatul Muti’ah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze Islamic education strategies in safeguarding students’ character against the negative impacts of the digital era. The digital age brings various conveniences as well as challenges, particularly concerning moral degradation due to unlimited access to harmful content. Islamic education plays a vital role in character building through a holistic approach that includes the teaching of moral values, exemplary behavior, worship habituation, and positive use of technology. This research employs a qualitative method with a library research approach to explore various literature related to Islamic educational strategies and the digital era’s influence on students. The findings indicate that integrated Islamic education strategies involving schools, families, and communities can develop students’ strong character, noble morals, and digital literacy. Continuous synergy and innovation in developing teaching methods and media are required to make Islamic education the primary defense in character formation in the digital age.